Effect of calcium carbonate whisker content on the morphology, crystallization, and mechanical properties of poly(para‐dioxanone)/Calcium carbonate whisker composites. Issue 12 (30th June 2015) - Bai, Yang; Liu, Xiangjun; Bai, Wei; Xiong, Chengdong
Abstract : In this work, poly( para ‐dioxanone) (PPDO) was mixed with 0, 1, 5, 10, 20, and 30 weight percent (wt%) calcium carbonate (CaCO3 ) whiskers by solution coprecipitation. Samples were compression molded into bars using a platen vulcanizing press. It has assessed the influence of the CaCO3 whisker content on the morphology, thermal, mechanical, and crystalline properties of the PPDO/CaCO3 whisker composites, using differential scanning calorimetry (DSC), polarized optical microscopy, scanning electron microscopy, and X‐ray diffraction. DSC showed that the glass transition temperature ( T g ) and crystallization temperature ( T c ) of the composites increased with increasing CaCO3 whisker content. At low CaCO3 whisker content (1 wt%), the degree of crystallinity ( D c) of PPDO increased sharply. The addition of higher content of CaCO3 whisker would cause more agglomeration in PPDO matrix, so that the mechanical properties of PPDO/CaCO3 whisker composites would gradually decrease. The mechanical properties of PPDO were changed by the presence of CaCO3 whiskers; the optimal amount of CaCO3 whisker was 1 wt%, which sharply improved the tensile strength of PPDO by 54%. POLYM. COMPOS., 37:3442–3448, 2016. © 2015 Society of Plastics Engineers